Synthesis of galacto-oligosaccharides derived from lactulose by wild-type and mutant β-galactosidase enzymes from Bacillus circulans ATCC 31382. (30th July 2018) - Yin, Huifang; Dijkhuizen, Lubbert; van Leeuwen, Sander S.
Abstract: Oligosaccharides derived from lactulose (β-D-Gal p -(1 → 4)-D-Fru) are drawing more and more attention nowadays because of their strong resistance to gut digestion, and the interest to discover novel prebiotics. Compared to galactooligosaccharides, currently known structures of lactulose oligosaccharides are very limited. In this study, the wild-type β-galactosidase BgaD-D of Bacillus circulans ATCC 31382, as well as the derived mutant R484H, were used to synthesize oligosaccharides from lactulose. In total, 9 oligosaccharide structures were identified by MALDI-TOF-MS and NMR spectroscopy analysis. Trisaccharide β-D-Gal p -(1 → 4)-β-D-Gal p -(1 → 4)-D-Fru was the major structure produced by the wild-type enzyme, while the R484H mutant showed a preference for synthesis of β-D-Gal p -(1 → 3)-β-D-Gal p -(1 → 4)-D-Fru. Our study greatly enriched the structural information about oligosaccharides derived from lactulose. Graphical abstract: Image 1 Highlights: GOS synthesized from lactulose by Bacillus circulans β-galactosidase. WT enzyme synthesized 5 structures. R484H mutant enzyme synthesized 9 structures. Characterized structures show 6 novel compounds. Lactulose-GOS yields up to 33.8% (w/w).